PORTRAYING HOW GENRE-BASED APPROACH WAS EMPLOYED BY EFL TEACHER UNDER KURIKULUM MERDEKA - Lestari, Nisi Bunga; Adia, Ahmad; Nirwana, Putri; Mapgun, Jumli Alam (IPI Garut Press, 2023)
Merdeka Curriculum is a newly implemented curriculum in Indonesia, making it an important topic for discussion, particularly regarding the teaching approaches. However, there is limited research related to this matter. Therefore, this study aims to investigate the teaching approaches employed under Merdeka Curriculum. This qualitative research adopts a study design and involves observation. The data are gathered from an English teacher in one of the junior high schools that has implemented Merdeka Curriculum. The findings indicate that the teacher implemented the Genre-based Approach in the EFL classroom, which is recognized by Merdeka Curriculum. However, it was found that one crucial stage known as the Joint Construction of the Text (JCoT) was missing in the implementation, and the teacher did not provide feedback to students. Therefore, it is important for teachers to incorporate various pedagogical strategies. These include visualization techniques, instructional house training, collaborative lesson study, and evidence-based professional development approaches like attending genre-based teaching workshops or seminars. By integrating these measures into their teaching repertoire, teachers can optimize their instructional practices and create a more motivating learning environment for students.